2020
DOI: 10.1146/annurev-micro-011720-122807
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis of Hydrogenotrophic Methanogenesis

Abstract: Most methanogenic archaea use the rudimentary hydrogenotrophic pathway—from CO2 and H2 to methane—as the terminal step of microbial biomass degradation in anoxic habitats. The barely exergonic process that just conserves sufficient energy for a modest lifestyle involves chemically challenging reactions catalyzed by complex enzyme machineries with unique metal-containing cofactors. The basic strategy of the methanogenic energy metabolism is to covalently bind C1 species to the C1 carriers methanofuran, tetrahyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 134 publications
0
27
0
Order By: Relevance
“…Microbial Protein Structure Group, Max Planck Institute for Terrestrial Microbiology, 35043 Marburg, Germany. 2 Redox and Metalloprotein Research Group, Max Planck Institute of Biophysics, 60438 Frankfurt am Main, Germany. 3 Core Facility for Mass Spectrometry and Proteomics, Max Planck Institute for Terrestrial Microbiology, 35043 Marburg, Germany.…”
mentioning
confidence: 99%
“…Microbial Protein Structure Group, Max Planck Institute for Terrestrial Microbiology, 35043 Marburg, Germany. 2 Redox and Metalloprotein Research Group, Max Planck Institute of Biophysics, 60438 Frankfurt am Main, Germany. 3 Core Facility for Mass Spectrometry and Proteomics, Max Planck Institute for Terrestrial Microbiology, 35043 Marburg, Germany.…”
mentioning
confidence: 99%
“…In hydrogenotrophic methanogenesis, water is the source of hydrogen in methane for most reactions converting CO 2 to methane. This includes the reduction of methenyltetrahydromethanopterin (methenyl-H 4 MPT) to methylene-H 4 MPT, and of methylene-H 4 MPT to methyl-H 4 MPT, reactions mediated by hydride transfer from reduced coenzyme F 420 (Shima et al, 2020). Although regeneration of F 420 H 2 is catalysed by a hydrogenase, this reaction is subjected to isotope exchange with H 2 O hydrogen (Löffler et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Although regeneration of F 420 H 2 is catalysed by a hydrogenase, this reaction is subjected to isotope exchange with H 2 O hydrogen (Löffler et al, 2019). H 2 is used directly as a reactant only by H 2 -forming methylene-H 4 MPT dehydrogenase, which is expressed particularly under Ni-limiting conditions (Shima et al, 2020). However, even this reaction, which also involves a hydride transfer, is affected by isotope exchange with water (Klein et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…However, analysis of clostridial hydrogenase II revealed that it contained no nickel and only iron. These two classes of enzyme differ phylogenetically [42] and to this was added a third broad class of iron-only hydrogenases found so far exclusively in certain methanogenic archaea [43]. The hydrogenases of clostridia and single-celled eukarya such as Chlamydomonas reinhardtii have in common that they lack [NiFe]-hydrogenases.…”
Section: A View Of the Biohydrogen Field 75 Years Onmentioning
confidence: 99%